WARPFIELD population synthesis: the physics of (extra-)Galactic star formation and feedback-driven cloud structure and emission from sub-to-kpc scales - Pellegrini, Eric William; Reißl, Stefan; Rahner, Daniel; Klessen, Ralf S.; Glover, Simon; Pakmor, Rüdiger; Herrera-Camus, Rodrigo; Grand, Robert J. J. (Monthly notices of the Royal Astronomical Society, 2020)
We present a novel method to model galactic-scale star formation and emission of star clusters and a multiphase interstellar medium (ISM). We combine global parameters, including star formation rate and metallicity, with the 1D cloud evolution code warpfield to model the sources of feedback within a star-forming galaxy. Within individual star-forming regions, we include stellar evolution, stellar winds, radiation pressure, and supernovae, all coupled to the dynamical evolution of the 1D parental cloud in a highly non-linear fashion. Heating of the diffuse galactic gas and dust is calculated self-consistently with the age-, mass-, and density-dependent escape fractions of photons from these fully resolved local star-forming regions. We construct the interstellar radiation field, and we employ the multifrequency radiative transfer code polaris to produce synthetic emission maps for a one-to-one comparison with observations. We apply this to a cosmological simulation of a Milky-Way-like galaxy built-up in a high-resolution MHD simulation of cosmic structure formation. From this, we produce the multiscale/phase distribution of ISM density and temperature and present a synthesized all-sky H  α map. We use a multipole expansion to show that the resulting maps reproduce all observed statistical emission characteristics. Next, we predict [S iii] 9530 Å, a key emission line that will be observed in several large forthcoming surveys. It suffers less extinction than other lines and provides information about star formation in very dense environments that are otherwise observationally inaccessible optically. Finally, we explore the effects of differential extinction, and discuss the consequences for the interpretation of H α emission at different viewing angles by an extragalactic observer.